Layʻ tī Cha rā toʻ Bhu rāʺ krīʺ cī raṅʻ toʻ mū ʼapʻ so Nuiṅʻ ṅaṃ khrāʺ pucchā ʼa phre poṅʻʺ khyupʻ : 9 kyamʻʺ tvai - Ñāṇa, Ledi Cha rā toʻ, 1846 or 7-1923 or 4. (Haṃsāvatī Piṭakatʻ Puṃ nhipʻ tuikʻ, 1956)
Authorʼs answers to questions on Buddhism, posed to him by some foreign scholars.